Association of atherogenic index of plasma and triglyceride glucose-body mass index and sarcopenia in adults from 20 to 59: a cross-sectional study - Pan, Ruirong; Wang, Tingwei; Tang, Ruixue; Qian, Zifan (Frontiers in Endocrinology, 2024)
Background The relationship between atherogenic index of plasma (AIP) and triglyceride glucose-body mass index (TyG-BMI) and sarcopenia has not been studied in the United States (US) population. Methods This research included 4,835 people from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2018. The relationship between sarcopenia and TyG-BMI, as well as the AIP index, was examined through the utilization of restricted cubic spline (RCS) analysis, subgroup analysis, and multivariate logistic regression analysis. Diagnostic value of AIP and TyG-BMI for sarcopenia was compared by receiver operating characteristic (ROC) curves. Results In this research, 428 people with sarcopenia were identified among the 4,835 subjects that were included in the experiment. AIP and sarcopenia were positively associated with an odds ratio (OR) of 1.58 and a 95% confidence interval (CI) of (1.07, 2.34) on fully adjusted multivariate logistic regression analysis. Similarly, TyG-BMI and sarcopenia were positively associated with an OR of 8.83 and a 95% CI of (5.46, 14.26). AIP and sarcopenia had a non-linear positive connection (P-value<0.001, P-Nonlinear=0.010), while TyG-BMI and sarcopenia had a linear positive correlation (P-value<0.001, P-Nonlinear=0.064), according to RCS analysis. Subgroup analyses showed a significant interaction between TyG-BMI and sarcopenia due to gender (P = 0.023). ROC curves showed that TyG-BMI (AUC:0.738, 95% CI: 0.714 - 0.761) was more useful than AIP (AUC:0.648, 95% CI: 0.622 - 0.673) in diagnosing sarcopenia. Conclusion In US adults aged 20–59 years, our study revealed a correlation between elevated AIP and TyG-BMI levels and heightened sarcopenia risk. Moreover, TyG-BMI has better diagnostic validity than AIP.